2006
DOI: 10.1200/jco.2006.07.1316
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Trial of Erlotinib in Gastroesophageal Junction and Gastric Adenocarcinomas: SWOG 0127

Abstract: Erlotinib is active in patients with GEJ adenocarcinomas, but appears inactive in gastric cancers. The molecular correlates examined were not predictive of the patient therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(178 citation statements)
references
References 22 publications
3
170
3
2
Order By: Relevance
“…A number of strategies against EGFR and HER-2 have been developed, including mAbs and smallmolecule kinase inhibitors (Mendelsohn and Baselga, 2003). There have been data from clinical trials demonstrating the results of applying anti-EGFR tyrosine kinase inhibitors (gefitinib or erlotinib) to oesophageal adenocarcinoma (Dragovich et al, 2006;Kwak et al, 2006), indicating that erlotinib may be active in patients with oesophageal adenocarcinoma and the useful molecular marker will be needed to predict the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…A number of strategies against EGFR and HER-2 have been developed, including mAbs and smallmolecule kinase inhibitors (Mendelsohn and Baselga, 2003). There have been data from clinical trials demonstrating the results of applying anti-EGFR tyrosine kinase inhibitors (gefitinib or erlotinib) to oesophageal adenocarcinoma (Dragovich et al, 2006;Kwak et al, 2006), indicating that erlotinib may be active in patients with oesophageal adenocarcinoma and the useful molecular marker will be needed to predict the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results from phase I/II studies of erlotinib plus FOLFOX or XELOX (Xeloda plus oxaliplatin) in advanced refractory colorectal cancer suggest that the addition of erlotinib to standard chemotherapy has some beneficial effects (123)(124)(125). Erlotinib has shown modest efficacy in patients with esophageal or gastroesophageal junction cancer, with response rates of 9% to 15%, but has shown no activity in patients with gastric cancer (126,127). A phase II trial of erlotinib in patients with unresectable hepatocellular carcinoma showed that 25% of patients remained progression-free at 4 months (128).…”
Section: Egfr Inhibitionmentioning
confidence: 99%
“…Anticancer drugs aimed at molecular regulators, including epidermal growth factor receptor (EGFR or HER1), its homologue c-erb-2 (HER2), have been developed and shown to be effective in the breast, lung, and colon cancers (Slamon et al, 2001;Thatcher et al, 2005;Gatzemeier et al, 2007;Sobrero et al, 2008). These drugs have been evaluated in advanced gastric cancer, but two EGFR tyrosine kinase inhibitors were found to be ineffective (Dragovich et al, 2006;Rojo et al, 2006).…”
mentioning
confidence: 99%